Engineering Properties, Processing and Value Addition of Tamarind: A Review - Bidyalakshmi, Thingujam; Sunita, Thongam; Kaukab, Shaghaf; Ravi, Y. (International Journal of Bio-resource and Stress Management, 2023)
Tamarind is widely consumed as fruit and spices in India. Tamarind contains pulp, seeds, shell and fibres. The pulp, which makes up between 30 and 50% of the mature fruit, is rich in reducing sugars, pectin, protein, fiber, and cellulose substances. Study of various physical engineering properties such as moisture content, fruit size, length, width, thickness, and weight (pulp, seed, shell, etc.) is important for designing the post-harvest machineries of tamarind. Major unit operations for processing of tamarind includes drying, dehulling, deseeding, pressing and storage. Traditional and mechanical approaches are used for these operations. Mechanical approaches of tamarind processing are carried out by dehuller and deseeder machinery. One of the crucial unit procedures in the processing of tamarind is deseeding which can be done by deseeder, mechanically. Processing of raw tamarind into value-added goods may increase its worth in addition to increase in shelf life. Additionally, it boosts the income of producers and processors. Value added products of tamarind are pulp, tamarind juice concentrate, tamarind pulp powder, tamarind pickle, tamarind jam, tamarind syrup, tamarind candy, tamarind kernel powder, dried fruit block, tamarind chutney and beverages. Tamarind is also rich in major amino acids phytochemicals and hence it carries the properties of antidiabetic, antibacterial, antivenomic, antioxidant. This paper provides an overview of the engineering properties, processing technologies, value added products, technologies and machineries developed/available for tamarind and its health benefits which will further help in machinery, protocol, technology and product design and development.